Active Chlorine Species Electrogenerated on Ti/Ru0.3ti0.7o2surface: Electrochemical Behavior, Concentration Determination and Their Application - Salazar-Gonzalez, R (Elsevier B.V., 2014)
In the present work, the evolution of chlorine-related species was investigated by cyclic voltammetric, polarization and electrolytic analyses in order to establish whether their formation and consumption related to either chemical or electrochemical reactions. This study was performed at Ti/Ru0.3Ti0.7O2anode by adding known concentrations of Cl-in solution by applying different current densities. The results demonstrated that dissolved Cl2, HClO, ClO-, chlorite, chlorine dioxide and chlorate can be electrochemically formed. The concentration trends of dissolved Cl2and chlorite indicated that the electrochemical route was responsible for their presence in the bulk solution, and these active species are responsible of the formation of the other chlorine species. By using Ti/Ru0.3Ti0.7O2as anode, the efficient treatment of real effluent was favored by applying 25, 50 and 75 mA cm-2in presence of NaCl (1.25 g L-1), achieving higher elimination of organic matter, ranging from 80% to 86%. Results clearly have demonstrated that the oxygen evolution inhibition depends predominantly on the specific electrochemical species formed in association with pH, nature of electrode and applied current. © 2014 Elsevier B.V. All rights reserved.